High-performance irreversibility field and flux pinning force density in BaHfO3-doped GdBa2Cu3Oy tape prepared by pulsed laser deposition. (15th January 2015) - Awaji, Satoshi; Yoshida, Yutaka; Suzuki, Takumi; Watanabe, Kazuo; Hikawa, Kazuyoshi; Ichino, Yusuke; Izumi, Teruo
Abstract: The high irreversibility field B i and strong flux pinning force were obtained for BaHfO3 -doped GdBa2 Cu3 O y tapes on a metallic Hastelloy substrate with an ion beam-assisted deposition MgO buffer layer. At 77.3 K, B i of 15.8 T and the maximum flux pinning force density of 23.5 GN/m 3 for B ∥ c were achieved for the 1.5 vol % BaHfO3 -doped GdBa2 Cu3 O y tape, which are the world's highest recorded values for REBa2 Cu3 O y -coated conductors on metallic substrates (RE = rare earth). From the flux pinning analysis, the c -axis correlated pinning by well-aligned BaHfO3 nanorods plays an important role in achieving the high irreversibility field and flux pinning force density performance.